2020
DOI: 10.1007/s12020-020-02460-9
|View full text |Cite
|
Sign up to set email alerts
|

Apparent mineralocorticoid excess caused by novel compound heterozygous mutations in HSD11B2 and characterized by early-onset hypertension and hypokalemia

Abstract: Purpose Apparent mineralocorticoid excess (AME) is an ultrarare autosomal recessive disorder resulting from deficiency of 11β-hydroxysteroid dehydrogenase type 2 (11βHSD2) caused by mutations in HSD11B2. The purpose of this study was to identify novel compound heterozygous HSD11B2 mutations in a Chinese pedigree with AME and conduct a systematic review evaluating the AME clinical features associated with HSD11B2 mutations. Methods Next-generation sequencing was performed in the proband, and Sanger sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…BMI1 [245], CCL5 [246], GREM1 [247], ANGPTL3 [248], ARG2 [249], MSRA (methionine sulfoxidereductase A) [250], SNCA (synuclein alpha) [251], NOX4 [252], PFKFB2 [253], PDZK1 [254], SUCNR1 [255], LYVE1 [256], AZGP1 [257], ERBB4 [258] and PLAT (plasminogen activator, tissue type) [259] might serve as molecular markers for kidney fibrosis. BMI1 [260], IGF2 [261], IRF7 [262], CCL5 [263], ACTN3 [264], E2F1 [265], PF4 [266], TEAD4 [267], TBX4 [268], GREM1 [269], CYP11B2 [270], WNT3A [124], COMP (cartilage oligomeric matrix protein) [271], FLI1 [272], RAP1B [273], ANGPTL3 [274], CYP3A5 [275], HSD11B2 [276], HMGCS2 [277], AGXT2 [278], SLC22A12 [279], FGF1 [280], CRY1 [281], PPARGC1A [282], SLC19A3 [283], CYP2C8 [284], ACOX2 [285], SLC2A9 [286], MSRA (methionine sulfoxidereductase A) [287], VNN1 [288], EPHX2 [289], CROT (carnitine O-octanoyltransferase) [290], SCNN1B [291], NR4A3 [292], HSD17B7 [293], SLC22A2 [294], AQP2 [295], SLC2A2 [296], EGF (epidermal growth factor) [297], ANGPT1 [298], SLC26A4 [299], KL (klotho) [300], SCNN1G [301], PDZK1 [302], PTPRD (protein tyrosine phosphatase receptor type D) [303], ACE2 [304], FOLH1 [305], SUCNR1 [306], GLCE (glucuronic acid epimerase) [307], AQP3 [308], DPP4 [309], REN (renin) [310], TRPM6 [311], ABCB1 [312], MTTP (microsomal triglyceride transfer protein) [313], CALCRL (calcitonin receptor like receptor) [314], ENPEP (glutamylaminopept...…”
Section: Discussionmentioning
confidence: 99%
“…BMI1 [245], CCL5 [246], GREM1 [247], ANGPTL3 [248], ARG2 [249], MSRA (methionine sulfoxidereductase A) [250], SNCA (synuclein alpha) [251], NOX4 [252], PFKFB2 [253], PDZK1 [254], SUCNR1 [255], LYVE1 [256], AZGP1 [257], ERBB4 [258] and PLAT (plasminogen activator, tissue type) [259] might serve as molecular markers for kidney fibrosis. BMI1 [260], IGF2 [261], IRF7 [262], CCL5 [263], ACTN3 [264], E2F1 [265], PF4 [266], TEAD4 [267], TBX4 [268], GREM1 [269], CYP11B2 [270], WNT3A [124], COMP (cartilage oligomeric matrix protein) [271], FLI1 [272], RAP1B [273], ANGPTL3 [274], CYP3A5 [275], HSD11B2 [276], HMGCS2 [277], AGXT2 [278], SLC22A12 [279], FGF1 [280], CRY1 [281], PPARGC1A [282], SLC19A3 [283], CYP2C8 [284], ACOX2 [285], SLC2A9 [286], MSRA (methionine sulfoxidereductase A) [287], VNN1 [288], EPHX2 [289], CROT (carnitine O-octanoyltransferase) [290], SCNN1B [291], NR4A3 [292], HSD17B7 [293], SLC22A2 [294], AQP2 [295], SLC2A2 [296], EGF (epidermal growth factor) [297], ANGPT1 [298], SLC26A4 [299], KL (klotho) [300], SCNN1G [301], PDZK1 [302], PTPRD (protein tyrosine phosphatase receptor type D) [303], ACE2 [304], FOLH1 [305], SUCNR1 [306], GLCE (glucuronic acid epimerase) [307], AQP3 [308], DPP4 [309], REN (renin) [310], TRPM6 [311], ABCB1 [312], MTTP (microsomal triglyceride transfer protein) [313], CALCRL (calcitonin receptor like receptor) [314], ENPEP (glutamylaminopept...…”
Section: Discussionmentioning
confidence: 99%
“…• Apparent Mineralocorticoid Excess (AME) Apparent Mineralocorticoid Excess (AME), more specifically known as Classic AME [51], is an infrequent monogenic hypertensive disorder with about 100 reported cases worldwide [52]. First reported in the 1970s [53], it was not until 1995 that the first mutation was found [52].…”
Section: Discussionmentioning
confidence: 99%
“…Primarily expressed in sodium-transporting epithelia, the HSD11B2 enzyme facilitates the metabolic conversion of cortisol to its inactive form, cortisone, at aldosterone binding sites thus protecting mineralocorticoid receptors (MRs) from cortisol excess [ 25 ]. In the compromised HSD11B2 activity as a result of mutation, the MRs were overstimulated by cortisol causing intense water and sodium retention, hypokalaemia, and hypertension [ 26 ]. To date, about 40 causative mutations in the HSD11B2 gene have been recognized [ 27 ].…”
Section: Genetics Of Hypertensionmentioning
confidence: 99%
“…Utilizing the next-generation sequencing (NGS) and Sanger sequencing, Fan et al [ 26 ] found that a paternally inherited c.343_348del and maternally inherited c.1099_1101del variant were detected in exon 2 and 5 of a teenager with AME. Both mutations are characterized to result in Glu115 deletion, Leu116 deletion, a truncated 11 β HSD2 protein production, and Phe367 deletion.…”
Section: Genetics Of Hypertensionmentioning
confidence: 99%